Women and Political Leadership in Islam: Ma'nā-cum-Maghzā Critical Hermeneutic Study - Muhammad Fauzinuddin Faiz; Nurul Huda; Akhmad Khubby Ali Rohmad; Muhammad Solikhudin; Sheyla Nichlatus Sovia (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2023)
This paper describes and analyzes the textual-contextual hadīth on the prohibition of women’s leadership in the public sphere. This study is a critical hermeneutic with the theory of ma‘nā-cum-maghzā, by making the literal origin (historical meaning, explicit) the starting point for understanding the central message of the text (implied meaning). The results of this paper indicate that women may become leaders in public affairs because textually and linguistically, the word lan yufliḥ, which means ‘will not be successful,’ in the hadīth does not apply permanently (mu’abbad), but only temporally (mu’aqqat). Contextually, the hadīth prohibited women from becoming leaders because the condition of women at the time of the hadīth did not allow them to handle social affairs due to the lack of knowledge and experience and the existence of deceit and greed, which could happen to anyone who had ambitions of power, men as well as women. Meanwhile, nowadays, many women have the expertise, knowledge, and managerial-organizational experience to support these matters.